“Радник старости” як модель юридичної газети для нефахівців - Галаджун, Зоряна; Haladzhun, Zoryana (Видавництво Львівської політехніки, 2023)
Роль медіа визначається їх суспільним призначенням, і це, передусім, – інформувати та формувати громадську думку. Поділ преси за типом її аудиторії є одним із основних критеріїв класифікації медіа, де поряд із спеціалізованими виданнями для фахівців певної галузі є газети та журнали для нефахівців. Зазвичай, ці видання публікують фахову інформацію, намагаючись подати її у формі, зрозумілій для людини, що не володіє фаховими знаннями загалом та спеціальною термінологією, щоб максимально задовільнити її інформаційні запити. Свою увагу ми зосередили на інформаційно-аналітичній юридичній газеті для нефахівців юриспруденції – “Радник старости”, де в цікавій та зрозумілій формі подається інформація правничого типу. Важливим кроком для вивчення спеціалізованих видань, які різноаспектно висвітлювали юридичну проблематику, є визначення й аналіз їх тематико-типологічної специфіки. Дослідження суспільно-політичних умов для розвитку цього типу спеціалізованої преси, особливостей діяльності редакційних колегій, проблемно-тематичного увиразнення дає нам розуміння потреб ринку щодо інформаційних запитів і вимог суспільства в новітній історичний період, визначає необхідні компетенції авторського колективу щодо формування запотребованого аудиторією контенту юридичного спрямування, а також розкриває можливості існування самобутньої преси, яка жодною мірою не може бути українським аналогом інтернаціональної корпорації. Спеціалізована преса, що функціонувала й розвивалася в незалежній Україні, нині поступово приваблює дослідницьку увагу науковців. Однак корпус юридичних видань, що належать до спеціалізованої преси, донині залишається малодослідженим. Оскільки система законодавства кожної країни є своєрідною та оригінальною, то й вплив глобалізаційних процесів на такі видання є менш значним і здебільшого виявляється у формах подання інформації та платформах, на яких вони розміщені, а не на формованому контенті. Спеціалізована юридична преса для вузької аудиторії – в цьому випадку для неди торію, на яку орієнтувалися засновники газети, означуємо поняттям “нефахівці”, тобто особи, які не мають фахової юридичної освіти, однак у зв’язку з виконуваними завданнями повинні бути достатнім чином юридично грамотними. Мета дослідження – вивчення особливостей формування правових знань у газеті для нефахівців. Завдання дослідження – узагальнення досвіду редакції видання “Радник старости” (2016–2022) у творенні моделі юридичної газети для нефахівців. Тематико-типологічні особливості низки періодичних видань розглянуто у працях Т. Давидченко, В. Іванова, М. Недопитанського, Т. Хітрової та інших науковців. Більшість дослідників вказує, що найхарактернішими для спеціалізованої преси є параметри проблемно-тематичного спрямування та тип аудиторії. Т. Фісенко пропонує маркетинговий підхід розподілу таких часописів. Дослідниця В. Шевченко подає складники поділу журналів за читацьким призначенням, де виокремлює видання для фахівців, для широкого кола читачів та окремих груп читачів, але водночас зазначає, що журнали одного й того ж тематичного спрямування можуть бути призначені, як для фахівців, так і для широкого кола читачів. Типологію спеціалізованих видань докладно розглянуто у монографії “Ділова преса України” Л. Дудченко, в якій авторка відзначає, що “головним каталізатором розвитку ділових медіа є читацька аудиторія, готовність її до сприйняття економічної інформації”. Типологічну систему спеціалізованої медичної преси, в основні якої є два базисні принципи – аудиторний фактор та цілі комунікаційної діяльності – запропонував В. Садівн

The role of the media is determined by the irsocial purpose, which is primarily to inform and shape public opinion. The division of the pressa ccording to the nature of its audienceis one of the main criteria for classifying the media, where along with specialized publications for specialists in a particular field the reare newspaper sand magazines for non-specialists. As a rule, these editions publish professional information, trying to presentitin a formunderst and able to a person who does not have professiona knowledge in general and special terminology to satisfy his orher information needs to the maximum extent possible. We focused our attentionon the legal information and analytical newspaper for non-legal professionals – “Radnyk Starosty”, which presents legal information in an interesting and understandable form. An important step in the study of specialized publications that covered legal issues in various way sis to identify and analyze their thematic and typological specificity. The study of the socio-political conditions for the development of this type of specialized press, the peculiarities of the activities of editorial boards, and the problematic and the maticemp has is givesus an understanding of the markeneeds intermsofin for mationrequestsandrequirements of society in the modern historical period, determines the necessary competencies of the author’s team to create legal content demanded by the audience, and also reveals the possibilities of the existence of an original press that can not in any way be a Ukrainian analogue of an international corporation. The specialized press, which functioned and developed in independent Ukraine, is now gradually attracting the research attention of scholars. However, the corpus of legal publications belonging to the specialized press remainspoorly researched to day. Since the system of legislation of each country is unique and original, the impact of globalization processeson such publications is lesssignifi cant and is mostly manifested in the forms of information presentation and platforms on which they are placed, rather than in the content they produce. The specialized legal press for a narrowaudience – in this case, for non-legal professionals – has not been the subjec to fresearch by communication scholars in general, nor has the thematic and typological image of publications, in particular the news paper “Radnyk Starosty” (Kharkiv, 2016–2022), which was published for this readership, has been studied. Wedefine this audience, which the foundersof the news paper were focused on, by the concept of “non-specialists”, i. e. persons who do not have a professional legal education, but in connection with the tasks they perform must be sufficiently legally literate. The aim is to study the peculiarities of forming legal knowledgein a newspaper for non-specialists. The objectives are to summarize the experience of the editorial board of the publication “Radnyk Starosty” (2016–2022) in creating a model of a legal newspaper for non-specialists. Thematic and typological features of a number of periodical sareconsideredin the works of T. Davydchenko, V. Ivanov, M. Nedopytanskyi, T. Khitrova and other scholars. Most researchers point out that the main characteristics of the specialized press are the parameters of the problematic and thematic focus and the nature of the audience. T. Fisenko proposes a marketing approach to the distribution of such magazines. Researcher V. Shevchenko presents the components of the division of journals by readership, where she distinguishes publications for specialists, for a widerange of readers, and for certain groups of readers, but at the same time notes that journals of the same the maticfocus can be intended for both specialist sand a widerangeofreaders. The typology of specialized publications is discussed in detail in the monograph “Business Press of Ukraine” by L. Dudchenko, in which the author no test hat “the maincatalyst for the development of business media is the readershipan ditsreadines stoperceive economic information”. The typological system of specialized medical press, which is based on two basic principles: the audience factor and the goals of communication activity, was proposed by V. Sadivnychyi.
“Radnyk starosty” as a model of a legal newspaper for non-specialists
Keywords: "Радник старости”; юридична газета; преса України; інформаційно-аналітичне видання; журналістика; редакційна колегія; періодичність; тираж; тематика; рубрика; “Radnyk Starosty”; legal newspaper; press of Ukraine; information and analytical publication; journalism; editorial board; frequency; circulation; issues; section; 070.41; 353]; 342.25(477)"20"